2011
DOI: 10.1007/s13296-011-3010-2
|View full text |Cite
|
Sign up to set email alerts
|

Fracture prediction of welded steel connections using traditional fracture mechanics and calibrated micromechanics based models

Abstract: Fracture resistance is of primary concern in the seismic design of beam-to-column connections in steel moment resisting frames (SMRFs). Micromechanics based fracture models such as the void growth model (VGM) and the stress modified critical strain (SMCS) model provide alternative approaches for ductile fracture prediction by relating micro-mechanisms of void nucleation, growth and coalescence to macroscopic stresses and strains. In this study, the VGM and SMCS models were calibrated for Q345 structural steel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…According to this model, ductile crack initiation occurs when the equivalent plastic strain exceeds a critical value of the plastic strain corresponding to the void size exceeding a critical void size. Wang et al () examined VGM for the fracture prediction of beam‐to‐column connections in SMRFs; they showed that VGM can predict the fracture of welded connection with good accuracy. The crack initiation could be predicted with reasonable accuracy by defining a threshold value εeqvpl for the given stress–strain state (Kanvinde and Deierlein , Wang et al ).…”
Section: Results and Design Implicationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this model, ductile crack initiation occurs when the equivalent plastic strain exceeds a critical value of the plastic strain corresponding to the void size exceeding a critical void size. Wang et al () examined VGM for the fracture prediction of beam‐to‐column connections in SMRFs; they showed that VGM can predict the fracture of welded connection with good accuracy. The crack initiation could be predicted with reasonable accuracy by defining a threshold value εeqvpl for the given stress–strain state (Kanvinde and Deierlein , Wang et al ).…”
Section: Results and Design Implicationmentioning
confidence: 99%
“…Wang et al () examined VGM for the fracture prediction of beam‐to‐column connections in SMRFs; they showed that VGM can predict the fracture of welded connection with good accuracy. The crack initiation could be predicted with reasonable accuracy by defining a threshold value εeqvpl for the given stress–strain state (Kanvinde and Deierlein , Wang et al ). Ghobadi et al () showed experimentally and analytically that the seismic performance of T‐stiffener could be improved by modifying the T‐stiffener and beam flange connection; in their study, the rupture index and triaxiality ratio and equivalent plastic strain index were used as rupture indicators.…”
Section: Results and Design Implicationmentioning
confidence: 99%
“…To determine the function of D , 10 groups of standard tension experiments for Q235 steel have been conducted by Zhou et al and a nonlinear softening law of describing D is achieved, D0.5em=0.5em1.3trueu¯italicpltrueu¯fitalicpl7.6. To perform the above described elastic–plastic and failure constitutive laws of steel material, parameters of C 2 , m , K , and η 0 should be determined firstly. In this study, C 2 = 0.63, m = 0.18, and K = 700 are adopted based on standard tension test data of open round bar for Q235 steel. η 0 = 1/3 is used as discussed previously.…”
Section: Nonlinear Numerical Modeling and Verificationmentioning
confidence: 99%
“…To perform the above described elastic-plastic and failure constitutive laws of steel material, parameters of C 2 , m, K, and η 0 should be determined firstly. In this study, C 2 = 0.63, m = 0.18, and K = 700 are adopted based on standard tension test data [33,34] of open round bar for Q235 steel.…”
Section: Determination Of Failure Evolutionmentioning
confidence: 99%
“…The present work involves the study of the mechanical behaviour of a modified IPE 200 metal beam, one of the most common commercial beams, used in the construction of metal buildings, in order to provide for its incorporation in the initial stages of assembling a metal building [40][41][42]. The modification of beam IRE200 requires heat treatment and welding using conventional welding methods.…”
Section: Construction Of a Modified Welded Metal Beam And The Effect mentioning
confidence: 99%